The political caricature and its readers: México city, 1876-1888 - GANTÚS, Fausta (2007)
The discussions about the newspapers and its receptors are constant among those who study the Mexican press of the 19th century, once the phenomena of the circulation, reading and reception of the contents of the newspapers result in a subject which is difficult to be clarified because there is no enough information that helps to analyze the problem. When the newspapers include political caricature, the problem ismuch more complicated because there are no clues that help to measure, value and understand the impact of an image on the reader. In this context, in this article we propose to collaborate to the discussion with the intention to clarify some fundamental problems and propose some answers to it, trying to set universes of producers, the results aimed with their creations, peculiar characteristics of the graphic language, readers to whom they were directed and types and levels of reading determined by the satirical language of the images.